The initial training of general surgeons in Uruguay of the Third Millennium and Mercosur Contents and Programs - Crestanello, Francisco A (Cirugía del Uruguay, 2002)
Surgeon training is an investment, a sowing. Its results are appreciated after a time, sometimes quite long. The average quality of its products is one of the most important factors determining the quality of General Surgery at a time and in a place.